Business journalism and business analytics: practice, media type, creative method - Potrebin, Andrei V. (Journal of the Belarusian State University. Journalism, 2023)
This paper identifies the types of media that provide economic agents with information for decision-making based on the analysis of the concepts «business press», «business journalism», «economic journalism» and «analytical journalism». The author’s understanding of the creative method of business analytics develops on the concept proposed by B. V. Streltsov and takes into account the predominance of analytical content in the media. The author puts forward a hypothesis about the importance of analytical media content for the formation of social attitudes and the maintenance of economic culture in a post-industrial society.
Keywords: business press; business journalism; business analytics; quality media; creative method; social attitudes; analytical journalism; economic culture